The eclipsing binary millisecond pulsar PSR B1744-24A - Possible test for a magnetic braking mechanism - Ergma, E; Sarna, M (2001)
As presented by Nice et al. (2000), long-term timing of the eclipsing binary PSR B1744-24A shows that the orbital period of this system decreases with a time-scale of only similar to200 Myr. To explain the orbital period decay, which is much faster than that predicted by emission of gravitational waves only (similar to1000 Myr), we propose that the orbital evolution of this system is also driven by magnetic braking. If magnetic braking is to explain the rapid decay of the orbit, then the factor A characterizing the effectiveness of the dynamo action in the stellar convection zone in the magnetic stellar wind formula must be equal to 1.